Expression of influenza M2e-NP recombinant fusion protein in Escherichia coli BL21 (DE3) and its binding to antibodies - Tan, Mei Peng; Alitheen, Noorjahan; Tan, Wen Siang; Yap, Wei Boon (Multidisciplinary Digital Publishing Institute, 2022)
The current influenza vaccines only confer protection against the circulating influenza subtypes, therefore universal vaccines are needed to prevent upcoming influenza outbreaks caused by emerging influenza subtypes. The extracellular domain of influenza A M2 protein (M2e) is highly conserved among different subtypes of influenza A viruses, and it is able to elicit protective immunity against the viruses. The influenza nucleoprotein (NP) was used to display the M2e in this study due to its promising T-cell response and adjuvanticity. The M2e gene was fused to the 5′-end of the NP gene and then cloned into pRSET B vector. The DNA sequencing analysis revealed six point mutations in the M2e-NP fusion gene, including one mutation in the M2e peptide and five mutations in the NP. The mutations were reverted using PCR site-directed mutagenesis. The recombinant plasmids (pRSET B-M2e-NP and pRSET B-mM2e-NP) were introduced into Escherichia coli (E. coli) BL21 (DE3) for protein expression. The mutated and non-mutated proteins were subsequently expressed and named mM2e-NP and M2e-NP, respectively. The expression of mM2e-NP and M2e-NP was not affected by the mutations. The binding of anti-M2e antibody to the purified native mM2e-NP and M2e-NP also remained active. However, when the anti-NP antibody was tested, the signal produced by mM2e-NP was very weak. The results implied that the amino acid changes in the NP had adversely impacted on the conformation of mM2e-NP and subsequently affected the antibody binding. In light of the remarkable antibody binding to the M2e-NP fusion protein, this study highly recommends the potential of M2e-NP as a universal influenza vaccine candidate.